Dose-efficient in vivo X-ray phase contrast imaging at micrometer resolution by Bragg magnifiers - Spiecker, Rebecca; Pfeiffer, Pauline; Biswal, Adyasha; Shcherbinin, Mykola; Spiecker, Martin; Hessdorfer, Holger; Hurst, Mathias; Zharov, Yaroslav; Bellucci, Valerio; Faragó, Tomáš; Zuber, Marcus; Herz, Annette; et al. (Optica, 2023)
X-ray imaging enables the study of morphodynamic and physiological processes in living organisms. However, the required photon flux increases with the desired spatial resolution and with it the requirements for dose efficiency. We realize full-field imaging at micrometer resolution close to the highest possible dose efficiency. This is achieved by combining propagation-based phase contrast with Bragg crystal optics and a high-Z single-photon-counting detector, all designed for X-ray energies that allow minimal dose for a given image quality. We prove the superior imaging performance compared to conventional systems and, in particular, show a substantial increase in dose efficiency for high spatial frequencies that comprise the relevant high-resolution components of the image. We demonstrate the potential of the technique by a behavioral in vivo study of submillimeter-sized parasitoid chalcid wasps within their host eggs before and during emergence. The findings show that the technique opens up new possibilities for dose-sensitive studies at micrometer resolution, not only in life sciences but also in materials research.